Inferior alveolar neuropraxia following laryngeal mask use. Issue 1 (8th March 2016) - Liu, Christopher; Mathews, Abey Matthew Varughese
Summary: We report a patient with an inferior alveolar neuropraxia following the use of an LMA Proseal TM device. Inferior alveolar neuropraxia is a rare complication following use of a supraglottic airway device. Although it is often self‐limiting, it may cause considerable distress to the patient. We discuss previous reports of inferior alveolar neuropraxia following use of supraglottic airway devices and propose recommendations in order to prevent this complication.